Analisis Urgensi Tes Diagnostik Belajar pada Pendidikan - Fani Rahmasari; Ningsih, Sri Mutiara; Samsinar (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This literature study aims to analyze and synthesize literature on the urgency of diagnostic tests in education. Using a qualitative approach and content analysis, this study descriptively and analytically examines various relevant sources such as journal articles, theses, dissertations, and books obtained through systematic searches in electronic databases (Google Scholar, ERIC, ProQuest) with keywords and selection criteria set. Data analysis was carried out through reduction, presentation, interpretation of content, comparison, synthesis of findings, and drawing conclusions. The results of the study indicate that diagnostic tests play a crucial role as essential formative instruments in realizing quality and inclusive education. This test allows educators to deeply understand the individual learning needs of students, become the basis for personalizing learning, early identification of learning difficulties, and empowering students through specific information on areas of improvement. It is concluded that in the era of demands for quality and inclusive education, diagnostic tests are no longer an option but a basic need for educational units to provide optimal support for each student, creating a responsive, fair, and effective learning environment.